PENGARUH PENGGUNAAN MEDIA PAPAN PECAHAN TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS 3 SDN SANGKURIANG: PENGARUH PENGGUNAAN MEDIA PAPAN PECAHAN TERHADAP HASIL BELAJAR MATEMATIKA MATERI PECAHAN SEDERHANA PADA SISWA KELAS 3 SDN SANGKURIANG KAB.SUBANG - novianti, astri; Roheni; Abdul Sholeh (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2026)
This study aims to determine the effect of fraction board media on the learning outcomes of Mathematics on Simple Fraction Material at SDN Sangkuriang, Subang Regency. The problem is that students are unable to add fractions. This study uses quantitative with a quasi-experimental method in the form of a nonequivalent control group design. In this design, the population is divided into two groups, namely the experimental group that uses fraction board media and the control group that uses conventional methods. The population used is 32 students of grade 3 of SDN Sangkuriang. The instruments used are observation and tests. The results of the study that the fraction board media has an influence on the learning outcomes of mathematics on fraction material with an average pretest value of the control class being 54.86 and after being given treatment and then a posttest the average value is 68.40. While in the experimental class, the average pretest value is 58.68 then after being given treatment and given a posttest the average value is 79.17. Hypothesis testing is carried out using an independent sample t-test. In the SPSS 24 program, the hypothesis results obtained with a sig value of 0.000 < 0.05, so Ha is accepted and Ho is rejected. So the use of fraction board media has an effect on the learning outcomes of mathematics on simple fractions in grade 3 of SDN Sangkuriang.